The Effectiveness Of Morphological Awareness Training In Acquiring Vocabulary For English Foreign Language Learners - Ermy Dikta Sumanik; Esti Junining (Universitas Kanjuruhan Malang, 2015)
The aim of this study was primarily to investigate the effects ofmorphological awareness training in acquiring vocabulary of EFL’Learners. The design of this study was quasi-experiment design. The totalpopulation of this study was 263 studentsat the first grade from SMPN 2Singosari. The sample was 66 students consist of 33 students from classVIIE as control group and 33 students from class VIIG as experimentalgroup. There were two independent variable, control group andexperimental group. The experimental group received 5 lessons onstrategies whereas the control group did not. Vocabulary Measurement testthat adapted from Coxhead (2000) were used and descriptive statistics werereported. In this study the effectiveness of Morphological Awareness wasinvestigated by using independent sample t-test.The result showed thattcounted was lower than tcritical (-18.00<2.000) with P value 0.00 (df=64).The P value was less than 0.05 which it indicated that there is significantdifferences between control and experimental group.The result of thisstudy has shown that there was an effect of morphological awarenesstraining in acquiring students’ vocabulary. Also, the findings have shownthat students had motivation to practice their vocabulary ability.Morphological awareness also makes the learner more aware of the writingsystem.